PENGUATAN KAPASITAS PENGURUS PONDOK PESANTREN DALAM PEMAHAMAN SUBSTANSI POKOK UNDANG-UNDANG NO 18 TAHUN 2019 TENTANG PESANTREN DI PONDOK PESANTREN NURUSSALAM WALISONGO GOMANG - Mangkunegara, RM. Armaya; Harysart, Vivin Astharyna; Ciptono; Aziz, Nur; Jauhari, M. Fikri (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2024)
This study aims to strengthen the capacity of the management of Islamic Boarding Schools (Pondok Pesantren) in understanding the core substance of Law No. 18 of 2019 concerning Islamic Boarding Schools, specifically at Pondok Pesantren Nurussalam Walisongo Gomang. This law is crucial for advancing and protecting the existence of Islamic boarding schools in Indonesia. Therefore, a thorough understanding of this law is essential for the management of boarding schools to run their organization effectively and support the quality of education provided. This research employs a qualitative descriptive approach with a case study method. The study was conducted at Pondok Pesantren Nurussalam Walisongo Gomang, located in District X, Y Regency. The research sample includes the management of the boarding school, such as the head of the boarding school and several other administrators who are directly involved in the management and operations of the pesantren. Data collection techniques used include in-depth interviews, participatory observation, and documentary studies related to the implementation of Law No. 18 of 2019 at the boarding school. The results of the study show that the management of Pondok Pesantren Nurussalam Walisongo Gomang has a relatively good understanding of the core substance of Law No. 18 of 2019. However, there are still areas that need improvement, particularly in the technical aspects of implementing the regulation, such as funding and human resource management in the pesantren. Intensive and routine training related to this law is needed to address these shortcomings. Additionally, establishing discussion forums and consultations with competent authorities could also strengthen the understanding of the pesantren management. Strengthening the capacity of the management in this regard is not limited to theoretical understanding but also practical application in the daily activities of the pesantren. By fully understanding the regulation, the management can be more effective in carrying out their duties, improving the quality of education, and strengthening the pesantren’s position in the national education system. Overall, this study contributes to the development of the capacity of the management of Islamic boarding schools, specifically in understanding and implementing Law No. 18 of 2019. In the future, it is expected that there will be synergy between the government, pesantren, and the community to enhance the role of pesantren in producing morally upright and high-quality generations.